The evolution of local food environments within established neighbourhoods and new developments in Perth, Western Australia. (May 2019) - Bivoltsis, Alexia; Trapp, Gina; Knuiman, Matthew; Hooper, Paula; Ambrosini, Gina Leslie
Abstract: Temporal changes in the location of food outlets can result in disparities in the availability and access of food across geographic areas, contributing to health inequalities. This study used mixed linear models to investigate how the location of food outlets around the home evolved over time with respect to area-level socio-economic status (SES) and urban design within established neighbourhoods and new residential developments. Food outlet data (supermarket/greengrocers, convenience stores, café restaurants and takeaway/fast food) were sourced from commercial database listings (SENSIS Pty. Ltd.) in 2004, 2006, 2007, and 2011. Using 2468 addresses from the RESIDential Environments Project (RESIDE), in Perth, Western Australia (WA), a count of each food outlet type and percentage of healthy food outlets within a 1.6 km road network buffer around the home, along with the road network distance to nearest food outlet were generated relative to each address at each time point. Proximity to and count of all food outlets increased over time in both new developments and established neighbourhoods. However, unhealthy food outlets were always in greater numbers and proximity to the home. The percentage of healthy food outlets was significantly greater in established neighbourhoods compared to new developments at all four time points. There were significantly more food outlets, and within closer proximity to the home, in established neighbourhoods compared to new developments at each time point. In established neighbourhoods, there were more convenience stores, takeaway/fast food and café restaurants, a lower percentage of healthy food outlets, and closer proximity to convenience stores in lower compared to high SES areas. In new developments there were significantly less supermarket/greengrocers, a lower percentage of healthy food outlets and greater proximity to takeaway/fast food and café restaurants in low compared to high SES areas. New developments designed according to the WA government's "Liveable Neighbourhoods Community Design Guidelines" policy had significantly more of all food outlets compared to other new developments. As such, people living in new developments, and low SES areas of Perth, may be disadvantaged with poorer access to healthy food outlets and greater exposure to unhealthy food outlets. Future urban planning and policy should focus on providing incentives that support the early development of supermarkets and healthy food outlets within new developments and low SES areas of Perth. Highlights: The number and proximity of all food outlet types increased with time in new developments and established neighbourhoods. Greater numbers and proximity to unhealthy food outlets at each time point in new developments and established neighbourhoods. The percentage of healthy food outlets was greater in established neighbourhoods compared to new developments. There was a lower percentage of healthy food outlets in low compared to high socio-economic areas. Liveable developments had more of all food outlet types compared to Hybrid and Conventional development types.